Načelo previdnosti in primeri njegove uporabe v praksi - Klemenčič, Tina (Varstvo narave, 2010)
The precautionary principle is the fundamental principle of the European environmental policy, meaning that in the event of doubt the benefit of environmental protection prevails over any other interests. With an emphasis on nature conservation, the article presents the legislation that obligates the use of the precautionary principle and with it related polluters pay principle. With a summary of the key conclusions in an actual judgment, the ECCourt of Justice's standpoint on this subject is presented.
Keywords: environmental protection; načelo previdnosti; Natura 2000; ohranjane narave; varstvo okolja